The influence of anger-arousal level on attribution of hostile intent and problem solving capability in an individual with a mild intellectual disability and a history of difficulties with aggression - MacMahon, K; Jahoda, A; Espie, C; Broomfield, N (2006)
Background Recent studies have suggested that cognitive biases may play an important mediating role in aggressive outbursts from people with mild intellectual disabilities (IDs). Essentially, some individuals may frequently perceive other people as acting towards them in a hostile fashion. This biased perception may develop through repeated adverse experiences, and may make them more likely to respond, likewise, in an aggressive manner. These studies have led to the development of a cognitive behavioural model of aggression, incorporating factors both intrinsic and extrinsic to the individual. This study aimed to explore one facet of this model: a putative relationship between anger-arousal level, problem-solving ability and perception of hostile intent in others. Method Single-case methodology was utilized, and a 44-year-old man with a mild ID and a history of difficulties with aggression participated. A series of vignettes, containing potentially provocative social interactions, were read to the participant. His perception of hostile intent, and suggestions of possible behavioural responses were recorded as dependent variables. Anger-arousal was manipulated, through autobiographical recall, as a dependent variable. Results Although not conclusive, results indicate that anger-arousal may act in an interactive fashion to increase perception of hostile intent. No effect of anger-arousal was observed on problem-solving ability; however, floor-effects in the task used may provide an explanation for this. Conclusions A high level of anger-arousal may exacerbate the probability of a frequently aggressive individual perceiving others as acting in a hostile manner. However, future research should take the limitations of this study into account, and continue development of a cognitive model of frequent aggression in those with a mild ID. © 2006 BILD Publications.